(untitled) (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2025)
Ayurveda extensively documents numerous medicinal plants and their therapeutic properties, but the lack of precise botanical descriptions often results in regional substitutions without scientific validation. Marsdenia tenacissima is identified as the botanical source of Murva in the Ayurveda Pharmacopoeia of India (API), while Chonemorpha fragrans is commonly used as its substitute in Southern India. This study evaluates the suitability of C. fragrans as an alternative to M. tenacissima through pharmacognostic, physicochemical, and preliminary phytochemical analyses of their aqueous and hydroalcoholic extracts. High-performance thin-layer chromatography (HPTLC) and Gas Chromatography-Mass Spectroscopy (GC-MS/MS) were employed for fingerprint profiling. The study revealed distinct morphological differences: M. tenacissima roots were yellow-buff with a complex xylem structure, while C. fragrans roots were brown with white latex. Both plants exhibited glycosides and saponins, but alkaloids and phenols were exclusive to C. fragrans. Hydroalcoholic extracts of C. fragrans displayed a richer array of phytoconstituents. HPTLC analysis identified gallic acid in the aqueous extract of C. fragrans and the hydroalcoholic extract of M. tenacissima, with quercetin present in all extracts and beta-sitosterol exclusive to hydroalcoholic extracts. These findings suggest that C. fragrans could potentially substitute M. tenacissima in Ayurvedic formulations, but further pharmacological studies are necessary to confirm their therapeutic equivalence.